2008
DOI: 10.1186/1743-7075-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-hydroxy-beta-methylbutyrate (HMB) on exercise performance and body composition across varying levels of age, sex, and training experience: A review

Abstract: The leucine metabolite beta-hydroxy-beta-methylbutyrate (HMB) has been extensively used as an ergogenic aid; particularly among bodybuilders and strength/power athletes, who use it to promote exercise performance and skeletal muscle hypertrophy. While numerous studies have supported the efficacy of HMB in exercise and clinical conditions, there have been a number of conflicting results. Therefore, the first purpose of this paper will be to provide an in depth and objective analysis of HMB research. Special car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
3
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 99 publications
4
174
3
13
Order By: Relevance
“…), while increases in lean muscle mass, which increases the capacity of the body to produce force, accounts for a greater percentage of strength gain later on 13 . Currently, the ability of HMB to increase indices of strength has been attributed to the changes observed in lean mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), while increases in lean muscle mass, which increases the capacity of the body to produce force, accounts for a greater percentage of strength gain later on 13 . Currently, the ability of HMB to increase indices of strength has been attributed to the changes observed in lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in adults suggested that the use of this dose resulted in the greatest effects on muscle mass and muscle strength 21 . Also, when supplementing with HMB, current evidence suggests that 1 g of HMB should be consumed three times per day, for a total of 3 g of HMB daily 13 .…”
Section: Hmb Supplementation and Exercise Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…β-hydroxy-β-methylbutyrate (HMB) is a leucine metabolite used as a diet supplement in order to improve the efficacy of exercises and to gain skeleton muscle hypertrophy (29,30). It has been demonstrated that prenatal administration of HMB has a positive impact on the growth and development of farm animals (26,27).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…HMB exerts its effects through protective, anticatabolic mechanisms and has been shown to directly influence protein synthesis (Slater and Jenkins 2000). Possible mechanisms of action include reduced muscle damage due to stabilization of muscle cell membrane, modulation of protein degradation by inhibition of the ubiquitin-proteosome system, and upregulation of IGF-1 gene expression in the skeletal muscle, and the mTOR signaling pathway leading to protein synthesis (Wilson et al 2008;Zanchi et al 2010).…”
Section: Introductionmentioning
confidence: 99%